2017
DOI: 10.1111/edt.12347
|View full text |Cite
|
Sign up to set email alerts
|

Remote diagnosis of traumatic dental injuries using digital photographs captured via a mobile phone

Abstract: The precision of the remote diagnoses was comparable to the diagnoses conducted in person. The levels of interexaminer agreement were higher when clinical data were included with the images. Mobile phones may be an effective tool for capturing images that assist in the remote diagnosis of traumatic dental injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 40 publications
(108 reference statements)
1
28
0
7
Order By: Relevance
“…In this era of evidence-based dentistry, any diagnostic test before being used needs to be tested systematically and proved reliable 17 . The diagnosis of a traumatised tooth is conventionally arrived based on the clinicians' expertise in dental trauma and clinical examination is considered as gold standard for dental trauma diagnosis 18 . The radiographic or other investigations such as computed tomography (CT) along with clinical examination may help clinician to find the correct diagnosis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In this era of evidence-based dentistry, any diagnostic test before being used needs to be tested systematically and proved reliable 17 . The diagnosis of a traumatised tooth is conventionally arrived based on the clinicians' expertise in dental trauma and clinical examination is considered as gold standard for dental trauma diagnosis 18 . The radiographic or other investigations such as computed tomography (CT) along with clinical examination may help clinician to find the correct diagnosis 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Nuestro protocolo de teletriaje enfocado a urgencias dentales cobra importancia en situaciones hostiles (Binaisse et al, 2019), como hoy en día lo es la actual pandemia. El alto nivel de especificidad de la encuesta permite categorizar de forma rápida y simple qué tan urgente es el motivo de consulta (de Almeida Geraldino et al, 2017;Mohan, et al, 2018), evitando asistencias presenciales que no requieran tratamiento inmediato (Izzo et al, 2018). Asimismo, su nivel de legibilidad permitiría además de educar, una comunica-Tabla V. Áreas de especialización y desempeño de jueces expertos.…”
Section: Discussionunclassified
“…Previous studies have validated remote diagnosis through images and have shown that it was comparable to diagnosis conducted in person . This study expanded current knowledge by describing the development and piloting stages of a smartphone application for surveillance of TDI.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, the World Health Organization (WHO) has recently released a statement about the use of appropriate digital technologies for public health, which explicitly highlights the potential to obtain information directly from the public to support disease surveillance. 20 Consistent with this call from the WHO, the DTT was designed with a view toward operators who do not normally participate in TDI surveillance. As far as the authors are aware, this is the first study of a mobile phone for an evaluation of a mobile application for dental trauma surveillance.…”
Section: Discussionmentioning
confidence: 99%